Environmentalist concept of the civilization of life - Szumera, Grażyna (Folia Philosophica, 2004)
The possibilities of an elimination of causes that lead our civilization to degradation of natural and social environments and prevention of global catastrophe in consequence have to be searched for in the factors of consciousness. These include a philosophy that proposes a change of mentality, ideals, giving up the idea of controlling nature and people. It is a philosophy directed at the environment, which our life and chances of next generations’ survival depend on, i.e. eco-philosophy. Wiesław Sztumski is the author of the environmentalist concept. Environmentalism is a philosophy, which - suggesting a change of the way of thinking and guidance of ecological thinking - creates a chance of changes in the social environment of a man. This social environment - together with the natural environment - determines the existence of people. In environmentalism, a change of the attitude of a man towards the environment he lives in is possible; consequently, an environment perceived as hostile can be treated as friendly. It is also likely that a revolution of consciousness and personalities of people will take place on the basis of environmentalism, which will enable a transition from the civilization of death to the civilization of life.